ANNUAL INORGANIC MERCURY SPECIATION IN RIVER WATER DISTURBED BY CHLOR-ALKALI EFFLUENTS: ROLE AND COMPETITION OF LIGANDS (CL-, BR-, DOC) - Hissler, C.; Probst, J.L.; Mortatti, J. (Geochimica Brasiliensis, 2012)